Axiomatic Design for Lean-oriented Occupational Health and Safety systems: An application in shipbuilding industry. (October 2016) - Babur, Ferhat; Cevikcan, Emre; Durmusoglu, M. Bulent
Highlights: We provide an axiomatic design (AD) for OHS system under lean production principles. Standard Risk Model is integrated with Kinney Risk Assessment Method. The developed roadmap by AD was planned to apply in a real life shipyard system. Abstract: The use of facilities provided by industrialization and technological developments has led to increase in occupational diseases and accidents in workplaces. A sheer success in Occupational Health and Safety (OHS) is possible when safety activities for employees, production and business are considered synchronously. OHS systems, where scientific research oriented technological advances applied, are required to be designed with the aim of preventing OHS related problems and their effects in sustainable manner. In this study, a systematic approach is proposed for design of Lean-oriented OHS systems by using Axiomatic Design principles. A holistic roadmap is obtained as the output of the study for the application of OHS system to a production system. The proposed OHS system design is applied to a real life shipyard system from shipbuilding industry and its feasibility is demonstrated.